The haemoglobinopathy survey: The reality of transfusion practice in sickle cell disease and thalassaemia in England. Issue 6 (25th October 2020) - Trompeter, Sara; Estcourt, Lise; Mora, Ana; Wong, Esther; Collett, David; Bolton‐Maggs, Paula; Poles, Debbi; Deary, Alison; Watt, Alison
Summary: Objectives: To establish, in an unselected population of London haemoglobinopathy patients, transfusion requirements, blood antigens/alloantibodies, transfusion modalities, burden of transfusion reactions and donor exposure. Background: Haemoglobinopathy patients are among the most highly transfused patient populations, and the overall population and number of patients on long‐term transfusion programmes are increasing. To provide a safe and efficacious transfusion service for patients, it is important to understand current practice, morbidity associated with transfusion, efficacy of different transfusion modalities and geno‐/phenotype requirements. Methods: Data on 4451 transfusion episodes in 760 patients from 12 London hospitals were collected retrospectively over a 6‐month period in 2011. Results: Alloimmunisation prevalence was 17% for sickle cell disease (SCD) and 22% for thalassaemia, most commonly anti‐Rh/Kell/Kpa /Cw . Rh phenotypes differed between SCD (Ro r 59.8%/R1 r 15.9%/R2 r 15.6%) and thalassaemia (R1 R1 29.6%/R1 r 28.4%/R1 R2 15.4%). Recording of pheno‐/genotypes fell below recommendations. A 2‐weekly manual exchange and 3‐weekly automated exchange came closest to achieving presumptive targets. In adults with thalassaemia, the mean blood requirement was 36 units per year; for SCD, erythrocytapheresis was carried out every 7 weeks with 66 units; for manual exchange, it was 38 units every 4 weeks; and for simple transfusion, it was 30 units p.a. every 4 weeks. Conclusion: Transfusion modality choice was influenced by the resources available—children mostly received simple transfusions, and adults received erythrocytapheresis; the relationships between frequency of exchanges/transfusion modality/target HbA% were not simple, possibly reflecting the difference in recipient erythropoiesis and consequent transfusion modality selection bias; adherence to existing and current guidelines regarding geno‐/phenotyping was limited; and alloimmunisation had a low incidence and high prevalence in both disorders.